Branching Time Logic, Perfect Information Games and Backward Induction - Michael Magill; Giacomo Bonanno; Kristin Van Gaasback (University of California, Department of Economics, 1998)
The logical foundations of game-theoretic solution concepts have so far been developed within the confines of epistemic logic. In this paper we turn to a different branch of modal logic, namely temporal logic, and propose to view the solution of a game as a complete prediction about future play. We extend the branching time framework by adding agents and by defining the notion of prediction. We show that perfect information games are a special case of extended branching time frames and that the backward-induction solution is a prediction. We also provide a characterization of backward induction in terms of the property of internal consistency of prediction.
Keywords: 330